The Changing Fashion of Belt Accessories in the Southern Levant: Sixth- to Seventh-Century Belt Accessories from Shivta - Bollók, Ádám (Liber annuus, 2021)
Described and discussed in the present paper are eight belt buckles and belt ornaments as well as a possible die of the later 6th to 7th centuries and the Early Islamic period discovered at Shivta. Four of them belong to the large family of Byzantine openwork belt accessories of the later 6th and early 7th centuries, four date from the earlier 7th century, while one piece can be assigned to the Umayyad or early ‘Abbāsid period. In addition to the detailed scrutiny of individual pieces, their place in the evolution of Eastern Roman belt fashion and their assumed association with the military are also discussed. The paper concludes that on the strength of the formal traits of the Shivta buckles, a number of them were in all likelihood manufactured in the village. These buckles also allow a glimpse into the process of Christianisation among Shivta’s residents.